Self-Perceived Employability of Workers With Disability: A Case Study in an Educational Farm - Fantinelli, Stefania; Di Fiore, Teresa; Marzuoli, Alessia; Galanti, Teresa (Frontiers in Psychology, 2022)
Background: The job placement of persons with disability is often threatened by prejudices and stereotypes; even when they are employed, they have less qualified and less paid jobs. The aim of this study is to investigate the self-perceived employability in a sample of workers with disability, hypothesizing to find a good level of self-determination and a positive meaning of work. Method: Ten semi-structured interviews have been conducted, then applying a mix-method to the data analysis through the qualitative interpretation and the quantitative content analysis. Results confirmed what recent literature show about the need for job inclusiveness of persons with disability, also underlined a profound sense of satisfaction related to the job, strong identity, and empowerment derived by the job involvement. Conclusions: Practical implications are related to the job design procedure inspired by diversity management, in order to pay attention to each single diversity and ensure equity and inclusion.